COMPARISON BETWEEN EPLEYS MANEUVRE AND PROCHLORPERAZINE MALEATE IN TREATMENT OF BENIGN PAROXYSMAL POSITIONAL VERTIGO: Benign Paroxysmal Positional Vertigo - Niazi, Kashif Obaid Khan; Dastgir, Majid; Ashfaq, Muhammad; Qamar, Saad Bin; Malik, Kamran Zamurrad; Nayyar, Shadzad (Pakistan Armed Forces Medical Journal, 2015)
Objective: The objective is to compare the efficacy of Epley’s maneuver and vestibular sedative, prochlorperazine maleate in the management of benign paroxysmal positional vertigo (BPPV).Study Design: Randomized Control Trial.Place and Duration of Study: ENT department, Combined Military Hospital, Rawalpindi from 1st May 2011 to 1st November 2011.Patients and Methods: After consent, 60 patients of BPPV fulfilling the inclusion criteria were randomly allotted two groups. Group A was treated with Epley’s maneuver (n=30) while group B with prochlorperazine maleate (n=30). Outcomes were analyzed on disappearance of vertigo at follow-up examination.Results: 24 (80%) cases managed by Epley’s maneuver showed relief of symptoms while only 14 (47%) treated by prochlorperazine maleate showed recovery after 15 days.Conclusion: Epley’s maneuver was more effective than vestibular sedatives like prochlorperazine maleate in treating patients of BPPV.